The Effectiveness of Teaching Coping Skills in Posttraumatic Stress Effects’ Reductions amongst Adolescents Recovered from Corona Pandemic - Jozan, Azar; Fardin, MohammadAli; Sanaguye Moharer, Gholamreza (Applied Family Therapy Journal (AFTJ), 2021)
Aim: the present study aims at determining the effectiveness of teaching coping skills in posttraumatic stress reduction amongst the students recovered from corona pandemic. Methods: use has been made of a semi-experimental research method with pretest posttest and follow-up design and experimental-evidence groups. The study population included 7 to 12-year-old girl students recovered from Corona disease and schooling in intermediate course during 2021-2022 academic years in Bam City. Using convenience sampling method, 30 individuals were selected from amongst hospitalized students as well as the ones recovered from Corona pandemic and they were randomly placed in two groups, namely experimental and evidence, each containing 15 persons. The experimental group received Alexander’s training package (2002) in 12 45-minute sessions; the study instrument was posttraumatic stress disorder questionnaire designed by Weathers et al (1993). The obtained data were analyzed using repeated measures’ ANOVA. Results: the results indicated that teaching coping skills is effective in reducing the signs and symptoms of re-experiencing the harming traumatic accident (p=0.003, F=10.69), signs of emotional numbness (p=0.020, F=5.93) and signs of arousal and excitement (p=0.002, F=10.80) as figured out in the posttest stage and the effect was found persisting in the follow-up tests. Conclusion: based on the results of the present study, it is needed to perform training and treatment interventions in line with the reduction of psychological problems and corroboration of the positive psychological traits for coping with Corona disease. Thus, considering the high prevalence of the psychological and mental disorders and low resilience at the time of disease outbreak as well as the outcomes resulting thereof, psychological intervention should be made.